The role of oxygen vacancies of ABO3 perovskite oxides in the oxygen reduction reaction. Issue 5 (26th March 2020) - Ji, Qianqian; Bi, Lei; Zhang, Jintao; Cao, Haijie; Zhao, X. S.
Abstract : The oxygen reduction reaction (ORR) is one of the most important electrochemical reactions in energy conversion and storage technologies, such as fuel cells and metal–air batteries. Abstract : The oxygen reduction reaction (ORR) is one of the most important electrochemical reactions in energy conversion and storage technologies, such as fuel cells and metal–air batteries. However, the sluggish kinetics of the ORR is a key factor limiting the performance of these energy storage and conversion devices. Perovskite oxides are a promising family of electrocatalysts for the ORR because of their unique physical and chemical properties, such as variable crystal structure and non-stoichiometric chemistry. Studies have shown that the catalytic properties of perovskite oxides in the ORR are largely related to oxygen vacancies, which alter their electronic and crystal structures and surface chemistry. This review summarizes recent research advances on understanding the role of oxygen vacancies of the ABO3 perovskite oxides in catalyzing the ORR. With a brief introduction of perovskite oxides, approaches to creating oxygen vacancies in the ABO3 perovskite oxides and the role of oxygen vacancies in improving their catalytic performance for the ORR are discussed. Research perspectives in this important area are highlighted.